Signaling mechanisms in tumor necrosis factor alpha-induced death of microvascular endothelial cells of the corpus luteum - Rueda Bo R; Davis John S; Lynch Maureen P; Pru James K (BMC, 2003)
Abstract The microvasculature of the corpus luteum (CL), which comprises greater than 50% of the total number of cells in the CL, is thought to be the first structure to undergo degeneration via apoptosis during luteolysis. These studies compared the apoptotic potential of various cytokines (tumor necrosis factor α, TNFα; interferon gamma, IFNγ; soluble Fas ligand, sFasL), a FAS activating antibody (FasAb), and the luteolytic hormone prostaglandin F2α (PGF2α) on CL-derived endothelial (CLENDO) cells. Neither sFasL, FasAb nor PGF2α had any effect on CLENDO cell viability. Utilizing morphological and biochemical parameters it was evident that TNFα and IFNγ initiated apoptosis in long-term cultures. However, TNFα was the most potent stimulus for CLENDO cell apoptosis at early time points. Unlike many other studies described in non-reproductive cell types, TNFα induced apoptosis of CLENDO cells occurs in the absence of inhibitors of protein synthesis. TNFα-induced death is typically associated with acute activation of distinct intracellular signaling pathways (e.g. MAPK and sphingomyelin pathways). Treatment with TNFα for 5-30 min activated MAPKs (ERK, p38, and JNK), and increased ceramide accumulation. Ceramide, a product of sphingomyelin hydrolysis, can serve as an upstream activator of members of the MAPK family independently in numerous cell types, and is a well-established pro-apoptotic second messenger. Like TNFα, treatment of CLENDO cells with exogenous ceramide significantly induced endothelial apoptosis. Ceramide also activated the JNK pathway, but had no effect on ERK and p38 MAPKs. Pretreatment of CLENDO cells with glutathione (GSH), an intracellular reducing agent and known inhibitor of reactive oxygen species (ROS) or TNFα-induced apoptosis, significantly attenuated TNFα-induced apoptosis. It is hypothesized that TNFα kills CLENDO cells through elevation of reactive oxygen species, and intracellular signals that promote apoptosis.